Literasi Budaya: Memperkenalkan Budaya Sunda melalui Lomba Kreativitas Budaya - Kurniasih, Nuning; Erwina, Wina; Kusnandar, Kusnandar (Journal Of Human And Education (JAHE), 2025)
One of the challenges of new students is adapting to a new environment and culture, not least for new students of Universitas Padjadjaran (Unpad) who live in the Sundanese region. The Library and Information Science Student Association (Himaka) at the Faculty of Communication Sciences (Fikom) Unpad, organised a Sundanese cultural creativity competition as an effort to introduce Sundanese culture to new 2024 students. We participated in judging the competition as part of the Community Service Activity (PKM). The competition was held on 12 September 2024 and was attended by five groups. The attractions displayed by the five groups were Sundanese agricultural culture, Ketuk Tilu dance, bakakak hayam tradition procession, sapintrong and pencak silat. The aspects assessed were stage action, presentation material and delivery, and feedback from respondents. The judging results show that basically all groups have performed cultural attractions well, this competition has motivated students to learn about culture and the values in it. This can be seen from the presentation material and how to deliver the material well. By knowing Sundanese cultural values, students are expected to adapt, understand the way of life, language and social norms that apply in Sundanese.